Structure-function and rational design of a spider toxin Ssp1a at human voltage-gated sodium channel subtypes - Dongol, Yashad; Wilson, David T.; Daly, Norelle L.; Cardoso, Fernanda C.; Lewis, Richard J. (Frontiers in Pharmacology, 2023)
The structure-function and optimization studies of NaV-inhibiting spider toxins have focused on developing selective inhibitors for peripheral pain-sensing NaV1.7. With several NaV subtypes emerging as potential therapeutic targets, structure-function analysis of NaV-inhibiting spider toxins at such subtypes is warranted. Using the recently discovered spider toxin Ssp1a, this study extends the structure-function relationships of NaV-inhibiting spider toxins beyond NaV1.7 to include the epilepsy target NaV1.2 and the pain target NaV1.3. Based on these results and docking studies, we designed analogues for improved potency and/or subtype-selectivity, with S7R-E18K-rSsp1a and N14D-P27R-rSsp1a identified as promising leads. S7R-E18K-rSsp1a increased the rSsp1a potency at these three NaV subtypes, especially at NaV1.3 (~10-fold), while N14D-P27R-rSsp1a enhanced NaV1.2/1.7 selectivity over NaV1.3. This study highlights the challenge of developing subtypeselective spider toxin inhibitors across multiple NaV subtypes that might offer a more effective therapeutic approach. The findings of this study provide a basis for further rational design of Ssp1a and related NaSpTx1 homologs targeting NaV1.2, NaV1.3 and/or NaV1.7 as research tools and therapeutic leads.